2020
DOI: 10.1002/eji.201948420
|View full text |Cite
|
Sign up to set email alerts
|

Double‐faced implication of CD4+Foxp3+ regulatory T cells expanded by acute dengue infection via TLR2/MyD88 pathway

Abstract: Dengue infection causes dengue fever (DF) and dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). CD4 + Foxp3 + Tregs are expanded in patients during dengue infection, and appear to be associated with clinical severity. However, molecular pathways involved in Treg proliferation and the reason for their insufficient control of severe diseases are poorly understood. Here, dengue infection induced the proliferation of functional CD4 + Foxp3 + Tregs via TLR2/MyD88 pathway. Surface TLR2 on Tregs was responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
3
14
0
Order By: Relevance
“…As shown in Fig. 4A, Treg cells ratio in the spleen of TLR2 −/− mice were signi cantly lower than those in the WT mice, this is consistent with previous research(P < 0.0001) (George et al 2020). We also tested the expression of Foxp3 in the lungs of mice after infection with A.…”
Section: Tlr2 Plays a Crucial Role In Induces The Proliferation Of CDsupporting
confidence: 90%
See 3 more Smart Citations
“…As shown in Fig. 4A, Treg cells ratio in the spleen of TLR2 −/− mice were signi cantly lower than those in the WT mice, this is consistent with previous research(P < 0.0001) (George et al 2020). We also tested the expression of Foxp3 in the lungs of mice after infection with A.…”
Section: Tlr2 Plays a Crucial Role In Induces The Proliferation Of CDsupporting
confidence: 90%
“…Study showing that C. albicans results in immunosuppression via TLR2-derived signals that mediate increased IL-10 production and survival of Treg cells[ (Netea et al 2004)]. And current evidence showed that Dengue infection in uenced the proliferation of Treg cells through TLR2/MyD88 pathway [(George et al 2020)]. In our study, we found that TLR2 de cient mice have a signi cant decrease in Tregs of spleen ( Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Different TLRs have different functions [82][83][84]. TLR2 is an important pattern recognition receptor in Tregs [85,86] and TLR9 mainly plays a negative role in the regulation of allergic inflammation [87][88][89]. TLR4 not only relies on conserved sequences encoded by embryological genes to identify pathogenic microorganisms and activate innate immunity but also regulates adaptive immunity [90,91].…”
Section: Activation Of Tlrsmentioning
confidence: 99%